PERANAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA DAN PEREKONOMIAN MASYARAKAT DESA MEKARSARI KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - Adri Ariyulianti; Arwan Gunawan (KRISNA: Kumpulan Riset Akuntansi, 2023)
This study aims to analyze how the role of Village-Owned Enterprises in helping to increase Village Original Income and the economy of rural communities in Ngamprah District. The research method used is descriptive qualitative research. Data collection techniques used in this study were interviews, observation, and documentation. The results of this reset show that BUMDes Mulyasari has not been able to provide the results of its efforts for PADes and the economy of the village community as a whole, but the BUMDes Mulyasari is still trying to provide the best service to the people of Mekarsari Village.